Bromine and nitrogen co-doped tungsten nanoarrays to enable hydrogen evolution at all pH values. Issue 34 (17th August 2017) - Li, Qun; Han, Ce; Ma, Xiao; Wang, Dewen; Xing, Zhicai; Yang, Xiurong
Abstract : Introducing Br and N into metallic tungsten nanoarrays produces a corrosion resistance in W/BrN with high performance for HER at all pH values. The excellent activity, enhanced electrical conductivity, as well as large turnover frequency of W/BrN are attributed to the codoping of Br and N. Abstract : Introducing bromine and nitrogen into metallic tungsten nanoarrays produces a W/BrN electrocatalyst with high performance for the hydrogen evolution reaction (HER) at all pH ranges. Unlike the acid soluble metals (such as Fe, Co, Ni), the resultant W/BrN has successfully inherited the excellent corrosion resistance from pure metallic W, particularly in proton exchange membrane compatible acid electrolytes. However, more importantly, the W/BrN develops some outstanding electrochemical properties, such as enhanced electrical conductivity, optimized electronic properties, and large turnover frequency (TOF), after codoping with Br and N. Hence, the HER performance of W/BrN was higher by several orders of magnitude in current density than that of pure metallic W. To attain current density of 10 mA cm −2, the W/BrN only needs overpotentials of 148, 190 and 94 mV in acidic, neutral and alkaline conditions, respectively. In addition, we investigated the long-term stability of W/BrN in three electrolytes.